Achievement of National Education Standards as an Indicator of School Quality - Artia Sihombing; Gressya Pebriani Agatha Tamba; Kristi Debora Siagian (Journal of Educational Studies in Science, Technology, Engineering, Arts and Humanities, 2026)
One important indicator for evaluating the quality of education in Indonesia is the Achievement of the National Education Standards (SNP). Each educational unit must meet various aspects of the SNP, including the curriculum, the learning process, and evaluation results. This research aims to analyze the relationship between the achievement of the National Education Standards (SNP) and school quality, as well as its impact on student learning outcomes. Using quantitative methods, data were collected from several schools in various regions, including national exam results, graduation rates, and other relevant indicators. The research results indicate that there is a significant positive correlation between SNP achievement and the quality of education perceived by students and parents. Learning outcomes and community satisfaction levels are higher in schools that successfully meet the standards. These findings indicate that SNP can be an effective tool for improving the quality of education in Indonesia if implemented regularly. It is hoped that this research will provide recommendations for policymakers and education practitioners to improve school quality by adhering to the established educational standards.